Intraobserver and interobserver reliability of cone beam weightbearing semi-automatic three-dimensional measurements in symptomatic pes cavovarus. Issue 5 (July 2020) - Bernasconi, Alessio; Cooper, Lucy; Lyle, Shirley; Patel, Shelain; Cullen, Nicholas; Singh, Dishan; Welck, Matthew
Highlights: 3D biometrics are reliable for measuring hindfoot alignment in pes cavovarus. Aetiology of cavovarus did not affect reliability of 3D biometrics in our cohort. Severity of cavovarus did not affect reliability of 3D biometrics in our cohort. 3D biometrics proved reliable regardless of level of seniority of the surgeon. FAO seems superior to CO and HAA for measuring foot alignment. Abstract: Introduction: Pes cavovarus is a three-dimensional (3D) foot deformity. New 3D semi-automatic measurements utilising weightbearing computerised topography (WBCT) images have recently been proposed to assess hindfoot alignment, but reliability in pes cavovarus has never been investigated. The aim of this study was to assess intraobserver and interobserver reliability of the foot ankle offset (FAO), calcaneal offset (CO) and hindfoot alignment angle (HAA) in pes cavovarus. Methods: Anonymised WBCT datasets from 51 feet (17 Charcot-Marie-Tooth related cavovarus, 17 idiopathic cavovarus and 17 controls) were retrospectively reviewed. Three observers (two senior foot and ankle fellows and one orthopaedic resident) independently measured FAO, CO and HAA using dedicated software, with measurements repeated two weeks apart. Subgroup analysis was performed to assess whether aetiology or severity of varus deformity and level of seniority affected reliability. Results: Mean values for intra and interobserver reliability for FAO ( r = 0.98; ICC: 0.99), CO ( r = 0.97; ICC: 0.98) and HAA measurements ( r = 0.97; ICC: 0.98) were excellent. Subgroup analyses showed that FAO, CO and HAA's intra ( r / ρ range, 0.77–0.95) and interobserver (ICC range, 0.88–0.98) reliability remained excellent in patients with Charcot-Marie-Tooth related cavovarus, idiopathic pes cavovarus and normal feet, regardless of the severity of deformity. No difference was found in FAO, CO and HAA mean values from three observers ( p > 0.05 in all cases). Discussion: This study demonstrates that 3D semi-automatic measurements of WBCT images have excellent intra and interobserver reliability in the assessment of hindfoot alignment in pes cavovarus. Aetiology and severity of deformity, and level of seniority do not affect reliability of these measurements. Level of evidence: Level III, retrospective comparative study.